Development of E-LKPD Based on RADEC Learning Model (Read, Answer, Discuss, Explain, Create) Integrated with Socio-Scientific Issues to Train Students’ Scientific Argumentation Skills - Barokah, Wilda Lailatul; Akmalia, Hafidha Asni; Ruswan, Ruswan (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study aims to analyze the validity of the developed E-LKPD. The method used is (R&D) with a 4D development model. The sample in this study were 34 students of class X of SMA Negeri 12 Semarang and the sampling technique used was purposive sampling . The data collection instrument was a validation questionnaire assessed by expert validators of media, materials, learning methodology, scientific argumentation, teacher and student assessments. The percentage of validation results from media experts was 87.5%, material experts were 97.2%, learning methodology experts were 87.5%, scientific argumentation skills experts were 90.6%, and biology teacher assessments were 98%. The student readability test showed a percentage of 88%. Based on the results of the overall data analysis, it was concluded that the E-LKPD based on the RADEC model integrated with SSI to train scientific argumentation skills was declared valid and good for use in Biology learning.